The newsletter editor's handbook - Arth, Marvin (Newsletter Resources, 1997)
The Newsletter Editor's Handbook shows you tricks and techniques used by reporters to write in professional news style under tight deadlines; interview for quotes that create the perfect article; craft headlines, leads and captions that hook readers; manage your own string of reporters and volunteers; and avoid copyright and libel problems. This book also gives you the inside story on the latest uses of computer and online technology including how to find information fast on the Internet, write articles that fit perfectly on the page ... every time; and choose fonts and newsletter templates. Top it all off with a stylebook that answers your grammar and style questions and you'll see why The Newsletter Editor's Handbook is a favorite desktop reference.